The legal nature of the debt gift contract In Jordanian civil law compared to Islamic jurisprudence: A comparative study between Jordanian and Iraqi law - Al-Aqrabawi, Esam Hassan (International Journal of Psychosocial Rehabilitation, 2020)
The gift is held with an affiliation with acceptance, and it is carried out in the transferee and does not require registration unless the talented person is a car, ship or plane, then its holding requires registration if the talented person is a real estate, the enforcement of the gift contract against the contracting parties and others will depend on his registration in the Land Department within which the talented property is located. The donator may, with the idea of the donation remain, stipulate that the gifted person must perform a certain obligation, and this commitment is considered a substitute, and the gifted person must implement the duties imposed on him under the gift and conditional contract in the interest of the donor or one of his relatives. So if he violates these conditional duties without justification and these violation Great efforts were made by the donor, breaking the contract. The acceptance of recourse in the Jordanian Civil Law requires that there is no objection to recourse. We believe that the Jordanian legislator should interfere with amending some articles of the civil law included in the subject of this research, unlike the Iraqi legislator who mentioned a text on the gift of religion in the Iraqi civil law. But its provisions were scattered, besides that the texts of the gift were derived from Islamic jurisprudence but it was not clarified in Formulating its independent characteristics that distinguish it from the gift in general, in contrast to Jordanian law, the gift of religion is a legal behavior that arises with the sole will of the creditor, as it forfeits its right in return for the emergence of its commitment to this forgiveness, which is not claiming the debt.